Dealing with Cultural Identities: A Study of Nepalese Families in Tokyo - Singh, Mehta Kalu (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
In recent years, the Nepalese migrant population in Japan has increased exponentially. The number reached 88,951 in 2018, becoming the largest south Asian population in Japan. This number includes people in various visa categories: skilled labor, engineer, business, dependent, student and so on. The number of school children lies somewhere around 10,000. A child born and raised in a culture different to their parents’ culture goes through a complex cultural identity formation process. In this context, this paper explores children’s cultural identity development and promotion by migrant Nepalese families in Tokyo. In particular, it examines which cultural identities they are prioritizing and how they are developing host cultural identities while maintaining their native culture. The experiences of these migrant Nepalese parents were collected through in-depth interviews with 45 parents. The responses suggest that these parents are prioritizing the promotion of a Nepalese cultural identity for their child(ren). Parents focus on promoting and participating in Nepalese festivals, cooking Nepalese food at home, and meeting other Nepalese families in Japan. However, almost every parent expressed their desire for the development of a multicultural sense in their child(ren).